Sexism of Gender in Arabic Vocabulary and Its Influence in Social Culture - Muassomah Muassomah; Laily Fitriani; Penny Respati Yurisa (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This study aims to explain how the linguistic elements of Arabic language reflects the social life of its users or society. This qualitative research relies on Arabic words and sentences as the main data taken from literatures and other written documents. The collected data are analysed qualitatively using a sociolinguistic approach to explain how the society use the Arabic words or sentences in their social interaction. The research reveals that Arabic language is one of the international languageswhich has the highest content of gender sexism among other languages in the world. Each Arabic word and sentence contain a gender identity (masculine and feminine). The Arabic or sentences that have a masculine identity are strong, strong, primary needs, and independent; whereas, the Arabic words or sentences that have a feminine identity are more likely to have the characteristics of cleanliness, health, secondary needs, and dependent. It can be concluded that the mastery of Arabic language requires not only the understanding of its words and sentences, but also its users’ social life where the Arabic Language grows and develops. In other words, the use of Arabic language cannot be separated from the ideology, culture and social life of its users. Penelitian ini bertujuan untuk menjelaskan bagaimana unsur-unsur linguistik bahasa Arab menggambarkan kehidupan social masyarakat penggunanya. Penelitian kualitatif ini mengandalkan kata dan kalimat bahasa Arab sebagai data utama yang diambil dari literatur dan dokumen tulis lainnya. Data terkumpul dianalisis secara kualitatif dengan menggunakan pendekatan sosiolingistik untuk menjelaskan setiap kata atau kalimat bahasa Arab yang digunakan oleh sebuah komunitas masyarakat dalam interaksi sosial. Dalam penelitian terungkap bahwa bahasa Arab merupakan salah satu Bahasa internasional yang mengandung muatan seksisme gender paling tinggi di antara Bahasa-bahasa lain di dunia. Setiap kata dan kalimat bahasa Arab memuat identitas gender (maskulin dan feminine). Kata atau kalimat yang beridentitas maskulin memiliki sifat kokoh, kuat, kebutuhan primer, dan independen; sedangkan, kata atau kalimat yang beridentitas feminin lebih cenderung pada sifat yang berkaitan dengan ketertiban, kebersihan, kesehatan, kebutuhan skunder dan dependen. Dapat disimupulkan bahwa memahami bahasa Arab tidak cukup dengan memahami kata dan kalimatnya, namun perlu juga memahami kehidupan sosial masyarakat penggunanya di mana Bahasa Arab tersebut tumbuh dan berkembang. Dengan kata lain, Bahasa Arab tidak akan lepas dari ideologi, budaya dan kehidupan sosial masyarakat penggunanya. تهدف هذه الدراسة إلى وصف الرموز في اللغة التي تعرض المجتمع. اللغة العربية من اللغات الدولية التي تحتوي على أعلى المحتويات للتمييز الجنسي في العالم. و تحتوي اللغة العربية في كل كلمة على هوية جنس (ذكورية وأنثوية). تشرح هذه الدراسة أن الجمل ذات الهويات الذكورية لها احتياجات قوية، قوة، أولية، واستقلال. في حين أن الكلمات التي لها هوية أنثوية من المرجح أن تكون سمات تحتوي على أمور تتعلق بالنظام والنظافة والصحة والاحتياجات الثانوية و التبعية. و يستخدم منهج اللغة الاجتماعية، لشرح كل كلمة عربية، لأن اللغة هي طموح مجتمع في التفاعل الاجتماعي. و يشير هذا البحث إلى أن فهم اللغة لا يكفي لفهم كلمات ورموز اللغة فقط، ولكن من الضروري فهم المجتمع الاجتماعي حيث تنمو وتطور اللغة. بمعنى آخر، كانت اللغة العربية وفقا لإيديولوجية الناطقين و ثقافتهم و حياتهم الاجتماعي.